Participatory Communication of Industrial Workers in Supporting Intako Msme Branding : Komunikasi Partisipatif Pengerajin Industri dalam Mendukung Branding Umkm Intako - Nizal, Akhmad Marzuqi; Sinduwiatmo, Kukuh (Indonesian Journal of Innovation Studies, 2023)
The purpose of this study was to determine the participatory communication of industrial craftsmen in supporting the branding of Intako SMEs in Sidoarjo. Collecting data using interviews, observation and documentation. Data analysis was carried out by analysis according to Miles and Huberman which consisted of data reduction, data presentation and verification withdrawal. The results showed that in supporting the branding of Intako bags and suitcases, the Sidoarjo district industry and trade office supported the Small and Medium SME Industry, namely by providing training to craftsmen, these trainings included increasing skills that were more directed at their human resources, where craftsmen or entrepreneurs to improve their skills. Furthermore, the forms of participatory communication of industrial craftsmen in supporting the branding of Intako bags and suitcases are in the form of heteroglossia, dialogic, polyphony, and carnival. Heteroglossia communication is characterized by a lack of capital to buy raw materials, capital is the most important factor in the running of an MSME in which capital is used as the development of a business. Then from a dialogical perspective it emerged when group members attended training meetings and workshops. The participation of polyphony also emerged, namely when the training and workshop expressed ideas or opinions openly. And lastly, in terms of participatory communication, the carnival SME group of bag and suitcase craftsmen Intako also appeared at a promotional event held by the Industry and Trade Office of Sidoarjo Regency.